Increased oxidative stress with substantial dysregulation of genes related to oxidative stress and DNA repair after laparoscopic colon cancer surgery. (December 2020) - Watt, Sara Kehlet; Hasselbalch, Hans Carl; Skov, Vibe; Kjær, Lasse; Thomassen, Mads; Kruse, Torben A.; Burton, Mark; Poulsen, Henrik Enghusen; Gögenur, Ismail
Abstract: Surgical stress is followed by oxidative stress, where reactive oxygene species may act as regulators of pathways related to cancer cell survival and metastatic ability. Furthermore, reactive oxygene species may cause DNA and RNA damage. The aim of this study was to examine whether laparoscopic colon cancer surgery causes oxidative stress and dysregulation of related pathways. Methods: Patients undergoing elective laparoscopic surgery for colon cancer were included. Blood and urine samples were drawn on the day prior to surgery and on day 1 and 10 after surgery. Results: Twenty-six patients were included. Out of 140 genes previously identified as sensitive to regulation by reactive oxygene species, 46 were significantly differentially expressed on day 1 after surgery (FDR < 0.05). Upregulated genes were related to cellular immune suppression, proliferation, migration and epithelial to mesenchymal transition. Downregulated genes were related to IFN pathways and cytotoxic immunological reactions. Genes related to DNA repair were primarily downregulated on day one after surgery, and urinary excretion of 8oxdG was decreased on day two after (p = 0.004), and increased on day 10 after surgery (p = 0.01). Conclusion: Laparoscopic colon cancer surgery causes oxidative stress, and impaired DNA repair. Gene expression profiling indicates that reactive oxygen species may act as regulators of pathways related to increased risk of metastasis and cellular immune suppression after surgery. Measures of intracellular oxidative stress, indicates impaired DNA repair on day two after surgery, and sustained oxidative stress on day 10 after surgery. Highlights: Laparoscopic colon cancer surgery causes oxidative stress. Oxidative stress may increase cancer cell survival and metastatic ability through altered gene expression. DNA repair mechanisms are impaired after laparoscopic colon cancer surgery.